2017
DOI: 10.1002/nvsm.1588
|View full text |Cite
|
Sign up to set email alerts
|

Marketing expense and financial performance in arts and cultural organizations

Abstract: Nonprofit arts and cultural organizations use marketing to sustain viability. This study uses data from the Cultural Data Project to examine the effects of marketing on revenue in arts and cultural organizations. The current analysis demonstrates that total marketing expense is positively related to total revenue. Marketing expense used for fund‐raising positively influences donation income, as intended, whereas commercial income is not affected. Alternatively, marketing expense for programs positively influen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…We used corresponding t -statistics to estimate the effect sizes when studies (e.g., Marudas et al, 2014) only report a level of statistical significance, but not standard errors. 1 For those studies that reported parameter estimates that were not statistically significant (e.g., Lee et al, 2018), we recorded effect sizes as zero (see Note 1). We used z -statistics to calculate effect sizes when studies estimated models using maximum likelihood (e.g., Krawczyk et al, 2017).…”
Section: Methodsmentioning
confidence: 99%
“…We used corresponding t -statistics to estimate the effect sizes when studies (e.g., Marudas et al, 2014) only report a level of statistical significance, but not standard errors. 1 For those studies that reported parameter estimates that were not statistically significant (e.g., Lee et al, 2018), we recorded effect sizes as zero (see Note 1). We used z -statistics to calculate effect sizes when studies estimated models using maximum likelihood (e.g., Krawczyk et al, 2017).…”
Section: Methodsmentioning
confidence: 99%
“…Fundraisers require social marketing, while social marketers require fundraising. Both can now benefit from the DSC's brand-new edition of Marketing Strategy for Effective Fundraising, which includes insights, research, and best practices [18]. Fundraisers at all levels of an organization must understand and apply good Social Marketing concepts in order to develop and implement plans that are both long-term and short-term in nature.…”
Section: B Fundraisingmentioning
confidence: 99%
“…On the one hand, globalization has driven “multi‐lateral agents,” such as the World Bank and many charitable foundations, to increase their presence and influence all over the world (Mitchell, 2014). On the other hand, many less prominent NPOs are struggling to maintain financial sustainability while investing donations on marketing to enhance organizational performance (Lee, Ha, & Kim, 2018). Hence, most NPOs focus a great deal of effort on creating economic sustainability to gain the financial means needed to address social problems.…”
Section: Introductionmentioning
confidence: 99%